Studi Semiotika Teks Diskursus “China Threat” di Kalangan Elit Indonesia - Zudan Rosyidi; Abu Fanani; Murni Fidiyanti; Jauharoti Alfin (Jurnal Riset Komunikasi (JURKOM), 2024)
This research departs from the problem of discussions on Foreign Workers (TKA) and China's claims to parts of the North Natuna Sea (LNU) area. Actively several parties who are considered state actors, such as government officials and non-state actors such as politicians, academics, and also ordinary people shape this discourse. The research method used integrates text semiotic methods with post-structuralist securitization concepts. Semiotics is used to select and analyze signs in text and non-text form as well as post-structuralist securtization as a model in analyzing these signs.These actors produced a number of signs (signs) in the form of indices, icons and symbols which were narrated both orally and in writing to represent the discourse of the "Chinese Threat" in the Natuna and Foreign Workers (TKA) cases. The results of the analysis show that the signs produced in the Natuna case by government elites (state actors) are the same as non-government elites (non-state actors). The government is directing the Natuna case as a securitization issue. Different facts were obtained in the case of Chinese foreign workers. Non-government elites (non-state actors) have the same view that this problem must be considered as a threat and included in the securitization process. Several social signs such as the death of Indonesian workers, wage discrimination, and arbitrary treatment should be used by the government to frame the case of foreign workers as a discourse of securitization. On the other hand, government elites (state actors) construct a narrative that Chinese foreign workers are in accordance with statutory regulations.